Multikulturalizm a miłosierdzie - Jarosław Furtan (Wrocławski Przegląd Teologiczny)
This article describes the relations between Ch. Taylor’s concept of multiculturalism and the concept of mercy, viewed as a social principle, presented in the writings of John Paul II (Karol Wojtyła). The author tries to prove that multiculturalism based on the so-called politics of recognition can produce the desired outcome through application of the principle of mercy understood as actualization of dignity of human beings. In his essay titled The Politics of Recognition Ch. Taylor writes whether and how social groups can obtain recognition of their different cultural identity in the public space. He criticises the views of liberal democrats who believe that “citizenship” (of a country, of the world) could serve as a universal identity. He believes that it would not be possible, because all people are unique individuals who make decisions about their own lives. Human identity is not monological in nature, but it is shaped through dialogue with other people. Taylor develops his demand for recognition of identity in two directions: protection of fundamental rights of individuals as human beings and recognition of specific needs of individuals seen as members of particular cultural groups. The recognition of cultural identity of social groups is rooted in the dignity of human beings. Mercy, in turn, serves as a dynamism that actualizes that dignity.